ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) - Zuhra, Frissca Audia (Pusat P2M Politeknik Negeri Batam, 2023)
Initial Public Offering (IPO) can make changes for public companies and get additional capital. Investors can assess the company's financial performance by using financial ratios before and after the initial public offering consisting of Current Ratio, Debt Equity Ratio, Debt Asset Ratio, Total Asset Turn Over, Net Profit Margin, Return On Assets, Return On Equity. Assessment of company financial performance using financial reports using the purposive sampling method for energy sector issuers conducting initial public offerings in 2018-2019, data analysis techniques use descriptive test, Shapiro Wilk normality test, paired sample t-test and wilcoxon signed rank test. The results show that there are differences in financial performance after the IPO on the Debt Asset Ratio, Total Asset Turn Over, and Return On Equity. The result show there was no significant difference in financial performance after the IPO on the Current Ratio, Debt Equity Ratio, Net Profit Margin, and Return On Asset.